Democracia a Tribunal do Juri: uma análise a partir da instrumentalidade democrático-constitucional - Wagner, Laís Franciele de Assumpção (2021)
This Dissertation is part of the Social Relations and Dimensions of Power Research Line, having as its theme the study of democracy in the Popular Jury based on democratic-constitutional instrumentality. The theme is based on the following problem: Is it possible to affirm that social participation, within the scope of the Popular Jury, satisfies a concept of democracy in a concrete sense? The general objective is the study of democracy in the Popular Jury, with three specific objectives: (a) developing the study of democracy based on representation in the Popular Jury; (b) analyze democracy in the essentiality of the Jury Court and (c) format a meaning of democratic-constitutional instrumentality of the criminal process. Ferrajoli's constitutional democracy was used as a base concept. It was found that neoliberalism is a pathological factor that affects the foundations of democracy and its rationality invades the social imagination, creating a type of common subversion based on the device of effectiveness. It was found that neoliberal reason contributes to the desymbolization of institutions to the extent that it uses a dogmatic ideological discourse that, in the legal and political spheres, leads to democratic performative contradiction. The Popular Jury is fatally affected by these factors as they enter the social imagination, subverting popular self-determination through the original desymbolization of the institution, creating a symbolic power relationship, with the predominance of the most favored class to the detriment of the stereotyped and marginalized lower class. . Through the deductive method, it was possible to conclude that social participation in the jury does not correspond to democracy in a concrete sense, neither in its representativeness nor in its essentiality and that the constitutional instrumentality of the criminal process must undergo a resignification, adding- if the democratic factor, through a demos embodied by a rationality of the common, counterbalancing neoliberal rationality, as a discursive bet to strengthen the guarantor theory.